Sinus Disease following Total Laryngectomy: A Radiographic Review. (2nd September 2014) - Kidwai, Sarah M.; Parasher, Arjun K.; Agbetoba, Abib A.; Iloreta, Alfred M.; Govindaraj, Satish; Miles, Brett A.
Abstract : Objectives: (1) Compare the incidence of radiographic sinus disease before and after laryngectomy by retrospective analysis of preoperative and postoperative computed tomography (CT) scans. (2) Analyze the change in pre‐existing radiographic sinus disease via a subset analysis. Methods: A single‐institution retrospective chart review was conducted. Patients who received a total laryngectomy or total laryngopharyngectomy between 2002 and 2012 with preoperative and postoperative CT scans were included. The Lund‐Mackay (LM) Scores for each sinus as well as the total LM score were recorded for both scans. The assessment of differences in these scores is based on McNemar's statistic for each sinus and on a paired t ‐test for the total LM score. Results: Surgical removal of the larynx creates an anatomical disconnect between the sinonasal cavity and distal respiratory tract. Normal nasal airflow is disrupted, resulting in alterations to the nasal mucosa, mucociliary clearance, and nasal flora. While the incidence of sinonasal disease in patients undergoing total laryngectomy has been studied via subjective scoring methods, this study is the first to evaluate radiographic sinusitis via an objective measure by comparing Lund‐Mackay scores before and after total laryngectomy. There were no significant differences in the LM scores between preoperative and postoperative scans within each sinus ( P value >.05) or in the total LM score ( t statistic >0.56). Conclusions: In patients undergoing total laryngectomy, disruption in nasal airflow has been correlated with altered sino‐nasal physiology and decreased subjective symptoms. However, our study shows no significant change in radiographic evidence of sinonasal disease after laryngectomy.